2010
DOI: 10.1021/jp105895a
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Amperometric Cholesterol Biosensor Based on Graphene−Pt Nanoparticle Hybrid Material

Abstract: We describe the development of a highly sensitive amperometric biosensor based on the hybrid material derived from nanoscale Pt particles (nPt) and graphene for the sensing of H 2 O 2 and cholesterol. The biosensing platform was developed using the hybrid material and enzymes cholesterol oxidase and cholesterol esterase. Chemically synthesized graphene has been decorated with nanosized Pt particles. The electron microscopic measurements show that the Pt nanoparticles on graphene have an average size of 12 nm a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
126
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 279 publications
(134 citation statements)
references
References 68 publications
2
126
0
2
Order By: Relevance
“…A reliable, fast, accurate, and low level detection of H 2 O 2 has been the central task in various fields of analytical chemistry from environmental protection [23,24] to biosensors utilizing enzymes [25][26][27][28][29][30]. There are several disadvantages of the enzyme-modified electrodes, such as instability, high cost of enzymes and complicated immobilization procedure.…”
Section: Introductionmentioning
confidence: 99%
“…A reliable, fast, accurate, and low level detection of H 2 O 2 has been the central task in various fields of analytical chemistry from environmental protection [23,24] to biosensors utilizing enzymes [25][26][27][28][29][30]. There are several disadvantages of the enzyme-modified electrodes, such as instability, high cost of enzymes and complicated immobilization procedure.…”
Section: Introductionmentioning
confidence: 99%
“…It is observed that four interfering substances did not cause observable interference. Because the oxidation of ascorbate and urate on the unmodified electrode occurs at more positive potential (>0.40 V), the coexistence of these analytes would interfere the measurement of H 2 O 2 [39]. Obviously, the excellent selectivity of the biosensor was attributed to the contribution of a low-operating potential amperometric detection of cholesterol.…”
Section: Stability Reproducibility and Selectivity Of The Cholestermentioning
confidence: 99%
“…It should be noted here that, most of the cases GO/rGO mixed with ethanolic Nf solution either by ultrasonication or by stirring at room temperature to form homogeneous mixture and directly coated on electrode surface for further use [61][62][63][64][65][66]. Nf also can be used as layer film over the modified electrode to stabilized the electrode material [67].…”
Section: Chemical Polymerizationmentioning
confidence: 99%